P-652 Contribution of the D19S884 allele 8 of the FBN3 gene and the Hippo signaling to the reproductive and metabolic phenotype of PCOS patients. (30th June 2022) - Ramírez Martín, N; Romeu, M; Martínez, J; Peinado, I; Buigues, A; Marchante, M; Pellicer, A; Herraiz, S
Abstract: Study question: Does exist a correlation between the presence of D19S884 allele 8 (A8) and Hippo pathway dysregulation with the metabolic and ovarian PCOS profiles? Summary answer: The presence of the A8 allele affects insulin resistance and hyperandrogenism. Moreover, PCOS ovarian phenotype could be related to a dysregulation of Hippo pathway genes. What is known already: The specific D19S884 A8 allele of the FBN3 gene has been associated with an increased probability of polycystic ovarian syndrome (PCOS). D19S884 participates in FBN3 alternative splicing and produces Asprosin-3 and Fibrilin-3 proteins that may be related to PCOS clinical manifestations. Asprosin-3 has been recently identified as a glucose modulator and could be related to metabolic profiles of PCOS. Fibrilin-3 is an extracellular matrix protein, and together with a dysregulation of the Hippo pathway, could be responsible for constraining follicular growth in the PCOS ovaries. Study design, size, duration: Descriptive and cross-sectional study with 93 women (25-37 years old) undergoing an IVF cycle between 2019 and 2021 at Hospital la Fe (Valencia, Spain). Thirty patients were considered PCOS while the remaining sixty-three were non-PCOS controls. After recruitment women were screened for A8 allele, metabolic status, hormone profile and Hippo pathway genes. The IVF cycle parameters were recorded to determine their relationship with study variables. Participants/materials, setting, methods: Patients with two or more Rotterdam-criteria or with polycystic ovarian morphology (PCOM) were considered as PCOS. After signed informed consent, blood samples and cumulus cells were obtained at egg retrieval. Hormone and metabolic parameters were analyzed and the homeostasis model assessment of insulin resistance (HOMA-IR) established. Genomic DNA was isolated to assess the presence of A8 allele by capillary electrophoresis. The expression of Hippo pathway genes, BIRC1 and CCN2, was analyzed by Taqman qPCR assay. Main results and the role of chance: PCOS patients showed increased body mass index (Control:23.2±3.7; PCOS:25.3±4.5, p = 0.04) antimüllerian hormone levels (Control:17.7±7.7pmol/L; PCOS:39.7±22.9pmol/L, p = 0.00), antral follicle count (Control:15±7; PCOS:27±13, p = 0.001) and a reduced number of good quality embryos (Control:1.3±0.9; PCOS:0.8±1.0, p = 0.02). The A8 allele was detected in 15% of the recruited patients, with a 13% incidence in controls and 19% in PCOS. Interestingly, PCOS A8+ patients presented the PCOM phenotype. Women with the A8 allele (A8+) showed higher DHEAS levels (A8-:1899.7±1256.9; A8+:2642.5±555.2, p = 0.046) and free androgen index (A8-:1.1±0.8; A8+:2.0±1.2, p = 0.046) when compared to A8- ones. Similar results were obtained when the comparison was made according to clinical diagnose (Control A8+ vs. Control A8- and PCOS A8+ vs PCOS A8-). Moreover, the overall A8+ patients associated an increase in glucose levels (A8-:85.7±10.9mg/dL; A8+:93.0±6.01mg/dL, p = 0.02) and HOMA-IR (A8-:1.7±1.1; A8+:2.5±1.2). These metabolic findings were observed in control women with the allele but not in PCOS. The PCOS group showed a downregulation of CCN2 (Fold-change (FC): -3.8±9.1, p = 0.02) in cumulus cells. Interestingly, those women with the A8 allele showed downregulated BIRC1 levels (FC A8+: -2.7±4.8 and A8-: 0.2±2.7; p = 0.04). These gene dysregulations could be related with a deficient oocyte-cumulus communication, abnormal follicular growth and an ovarian stroma stiffness alteration. Limitations, reasons for caution: These promising results need to be confirmed in a larger population of PCOS to allow validation of the observed effects according to PCOS sub-phenotypes. Moreover, transcriptomic analysis and functional enrichment assays should be carried out to clarify the contribution of Hippo pathway and A8 allele to PCOS pathogenesis. Wider implications of the findings: The obtained results suggest that the presence of the A8 allele influences the metabolic profile related to insulin resistance and androgen levels, as well as the activation status of Hippo pathway. Moreover, this signaling pathway seems to be dysregulated in PCOS patients, suggesting its possible role in the ovarian phenotype. Trial registration number: Not applicable